PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT LAUTAN BENING BATAM - Brigida Endah Nuraeni, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
This research is made under the title "The Influence of Situational Leadership Style and Work Motivation on Employee Performance PT Lautan Bening Batam". The purpose this research is to find out how big the influence of Situation Leadership Style and Work Motivation on Employee Performance of PT Lautan Bening Batam. Data collection techniques used in this study in the form of research by distributing questionnaires and literature study. Methods in this study using quantitative research techniques. Population and sample determined are employees of PT Lautan Bening Batam with 62 respondents. The results of this study indicate that both alone, situation leadership style has a positive and significant effect on employee performance. The value of 0,000 situational leadership style significance is smaller than α = 0,05. Work motivation has an effect on significance of PT Lautan Bening Batam 0,034 is smaller than α = 0,05. Based on Beta value known that the variable that is dominant to employee performance is situational leadership style equal to 0,571 (57,1%). Together, situational leadership style and work motivation have a positive and significant influence on PT Lautan Bening Batam performance. This decision is based on the level of significance of F value of 30.452 with a significance level of 0.000 smaller than α = 0.05.